Interpreting Critical Incidents in Implementing a Multi-Tiered System of Supports through an Active Implementation Framework. Issue 3 (26th May 2020) - Charlton, Cade T.; Sabey, Christian V.; Young, Ellie L.; Moulton, Sara E.
ABSTRACT: A Multi-Tiered System of Supports (MTSS) is a framework for organizing and integrating academic, social, and emotional supports within a school. Full implementation of MTSS establishes a continuum of readily-available supports matched to student needs. Federal education statute and state-education agencies (SEAs) have prioritized the scale-up of MTSS as a means of improving student performance and the quality of the school learning environment. Our prior research into SEA MTSS scale-up projects identified critical incidents, that helped or hindered the success of these projects in 27 states. The purpose of this paper is to reexamine our findings using the active implementation framework to identify the linkages between the an implementation framework developed based on implementation science and critical incidents in the scale-up of MTSS. We provide recommendations to educational leaders and researchers. In addition, we provide commentary on the utility the active implementation framework as it applies to state scale-up and consider areas for future research.